Overexpression of β-Ketoacyl-CoA Synthase From Vitis vinifera L. Improves Salt Tolerance in Arabidopsis thaliana - Yang, Zhen; Yang, Xue; Dong, Shujia; Ge, Yao; Zhang, Xuenan; Zhao, Xinjie; Han, Ning (Frontiers in Plant Science, 2020)
Grape (vitis vinifera L.) is a fruit tree with high salt tolerance and high nutritional value, medicinal value and economic value. Suberin in roots is characterized by long-chain fatty acids and is thought to be related to the salt tolerance of grape. The key enzyme in the fatty acid elongation process is β-ketoacyl-CoA synthase (KCS). The function and the regulatory mechanism of VvKCS in response to salt stress in grape is unclear. In this study, VvKCS was isolated from Vitis vinifera L. A real-time quantitative polymerase chain reaction analysis showed that salt stress enhanced VvKCS transcription levels in grapes. Overexpression of VvKCS increased the tolerance to salt stress in Arabidopsis during the germination and seedling stages. The improved salt tolerance was the result of the combined contributions of multiple mechanisms including regulation of expression of ion transporters and channels, accumulating osmotic regulating substances and maintaining membrane stability. The results of this study are valuable information on plant salt tolerance and provide a theoretical basis for the molecular mechanism of grape salt tolerance.